TRACES OF SUFISM IN THE BUGIS LONTARA MANUSCRIPT - Nurkhalis A. Ghaffar; Asriyah Asriyah; Baso Pallawagau (International Conference on Social and Islamic Studies, 2021)
Manuscripts are classical intellectual treasures that describe various aspects of people's lives in the past. The media for writing Nusantara manuscripts are various, including Bugis Lontara. This paper will explain the Bahrullāhūt manuscript which contains the teachings of Sufism. The problem studied is how to describe Bahrullāhūt? and what is the content of Bahrullāhūt?. The method used is the philological method with research lines, namely an inventory of manuscripts, descriptions of manuscripts, transliteration and translation of manuscripts and analysis of these manuscripts. Presentation of research results using descriptive analysis. The results showed that the Bahrullāhūt manuscript was a single manuscript (codex unicus) because it had no variants. The manuscript is written in lontara script in Bugis language which can still be read clearly. Bahrullāhūt discussed the concept of Nur Muhammad which became one of the themes in sufism teachings. Nur Muhammad is the source of the creation of all beings who have two essences, namely the nature of awalareng or wilayah and the nature of nubuwwah. The concept of Nur Muhammad in Bahrullāhūt has a theological basis from the Qur'an and Hadith.